After the breakup: How divorcing affects individuals at work - Wanberg,Connie R.; Csillag,Borbala; Duffy,Michelle K. (Personnel Psychology, 2023)
Divorce is one of life’s most stressful events. By pairing two studies, using mixed-methods, and drawing on conservation of resources theory, we contribute new and previously unavailable information about three questions. How and to what extent does going through a divorce affect individuals at work? What factors differentiate a lower versus higher impact on work? Do work outcomes improve after a divorce has been completed? In Study 1, individuals currently in the process of divorcing report more negative mood at work, lower job performance, and lower health in comparison to employees recently divorced, divorced over five years ago, or never divorced. Qualitative findings illustrate first hand reports of intrusive negative affect and reduced focus at work. At the same time, nearly 39% of individuals reported that divorcing had a positive impact on their job, work, or career. Qualitative findings reveal that for some, divorcing frees up time and energy and amplifies motivation for work. Study 2 is a longitudinal survey study of individuals in the process of a divorce. Findings indicate that levels of divorce-related grief, quality of the dissolving marriage, the presence of children, and anticipated post-divorce financial stability differentiate between those with better and worse work outcomes. Individuals improve on work-related cognitive and physical engagement, job performance, and health after their divorces are completed. Our results extend empirical knowledge and theory with new insights about work outcomes associated with divorcing as well as the recovery of work outcomes over time.
Keywords: Management